Intensive glucose control improves kidney outcomes in patients with type 2 diabetes. - Perkovic, V; Heerspink, H; Chalmers, J; Woodward, M; Jun, M; Li, Q; MacMahon, S; Cooper, M; Hamet, P; Marre, M; Mogensen, C; Poulter, N; et al. (2013)
The effect of intensive glucose control on major kidney outcomes in type 2 diabetes remains unclear. To study this, the ADVANCE trial randomly assigned 11,140 participants to an intensive glucose-lowering strategy (hemoglobin A1c target 6.5% or less) or standard glucose control. Treatment effects on end-stage renal disease ((ESRD), requirement for dialysis or renal transplantation), total kidney events, renal death, doubling of creatinine to above 200 μmol/l, new-onset macroalbuminuria or microalbuminuria, and progression or regression of albuminuria, were then assessed. After a median of 5 years, the mean hemoglobin A1c level was 6.5% in the intensive group, and 7.3% in the standard group. Intensive glucose control significantly reduced the risk of ESRD by 65% (20 compared to 7 events), microalbuminuria by 9% (1298 compared to 1410 patients), and macroalbuminuria by 30% (162 compared to 231 patients). The progression of albuminuria was significantly reduced by 10% and its regression significantly increased by 15%. The results were almost identical in analyses taking account of potential competing risks. The number of participants needed to treat over 5 years to prevent one ESRD event ranged from 410 in the overall study to 41 participants with macroalbuminuria at baseline. Thus, improved glucose control will improve major kidney outcomes in patients with type 2 diabetes.